2017
DOI: 10.1016/j.euf.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

In-depth Critical Analysis of Complications Following Robot-assisted Radical Cystectomy with Intracorporeal Urinary Diversion

Abstract: In-depth critical analysis of complications following robot-assisted radical cystectomy with intracorporeal urinary diversion. European Urology Focus, (doi:10.1016Focus, (doi:10. /j.euf.2016 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/145598/ RESULTS AND LIMITATIONSThe 90-day all complication rate following ileal conduit and continen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
1
22
0
3
Order By: Relevance
“…A recent study analysed complications following RARC with intracorporeal urinary diversion in 134 cases and found that the majority of Clavien ≥III complications can be attributed to a surgical cause which may be related to surgeon experience [23]. In our meta-analysis of operating time, there was significant heterogeneity observed which may reflect a variation in surgical experience in RARC.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study analysed complications following RARC with intracorporeal urinary diversion in 134 cases and found that the majority of Clavien ≥III complications can be attributed to a surgical cause which may be related to surgeon experience [23]. In our meta-analysis of operating time, there was significant heterogeneity observed which may reflect a variation in surgical experience in RARC.…”
Section: Discussionmentioning
confidence: 87%
“…). Based on our present findings, we would hypothesise that the early management of postoperative complications may avoid a situation where ‘complications beget complications’ leading not only to a more challenging recovery and increased healthcare costs, but ultimately to increased rate of mortality as well .…”
Section: Discussionmentioning
confidence: 74%
“…Historic reports of ORC performed at high‐volume institutions reported a 58–64% 90‐day complication rate after surgery, with a 13–22% major complication rate . Previously, we reported a 90‐day all and major complication rate of 72% and 21%, respectively, with a median hospital LOS of 10.5 days in 134 consecutive iRARC cases . According to UK and USA population data, the mean LOS after cystectomy before the advent of ERAS was 19 and 11 days, respectively .…”
Section: Discussionmentioning
confidence: 90%